Baduanjin Exercise for Frailty Management in Frail or Prefrail Older Adults: A Systematic Review and Meta-Analysis - Jiaqi Zhao; Sharifah Shafinaz Sh Abdullah; Bing Liang; Ye Gao; Gufeng Wu; Zhicui Lu (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: This systematic review and meta-analysis evaluated the effects of Baduanjin, a traditional Chinese mind-body exercise, on frailty and multidimensional health outcomes in older adults. Methods: Following PRISMA guidelines, we systematically searched multiple databases for RCTs on Baduanjin in frail adults aged ?60 years. Data were pooled using fixed- or random-effects models to calculate MDs or SMDs with 95% CIs. Heterogeneity was quantified by the I² statistic, with random-effects models applied if I² > 50%. Publication bias was assessed by funnel plots and Egger’s test, with the trim-and-fill method used for adjustment when indicated. Results: Fifteen RCTs (n = 1,044) were included. Baduanjin significantly reduced frailty severity (SMD = -1.12; 95% CI: -1.59 to -0.65) and improved physical function outcomes, including grip strength (MD = 2.39 kg, 95% CI: 2.17 to 2.62, P < 0.001), 6-minute walking distance (MD = 33.72 m; 95% CI: 12.47 to 54.97), and short-distance walk time, although the pooled effect (MD = -0.31 s; 95% CI: -0.57 to -0.06) was moderated by test distance with significant heterogeneity. Mental health improvements encompassed reduced anxiety/depression (SMD = -0.73; 95% CI: -1.11 to -0.35) and enhanced sleep quality (MD = -2.48; 95% CI: -3.21 to -1.76). Cognitive function (MMSE: MD = 2.81; 95% CI: 0.11 to 5.51) showed a statistically significant improvement, though with wide confidence intervals. Quality of life (SF-12/SF-36: SMD = 0.75; 95% CI: 0.48 to 1.02) also improved significantly. Conclusion: Despite methodological limitations in the included trials, pooled evidence suggests that Baduanjin may confer clinical benefits for managing frailty in older adults. Given its simplicity, safety, and adaptability, Baduanjin should be considered for integration into standard geriatric care and community health programs.